Flow Cytometric Analysis of Mechanically Disaggregated Bone Marrow Trephine Biopsies. Issue 6 (22nd October 2018) - Wheeler, M.; White, G.; Brockie, S.; Dickson, M.; Weinkove, R.
Abstract : Background: Bone marrow (BM) aspirate analysis by flow cytometry (FC) is a key hematopathologic technique but dry taps hinder diagnosis. We describe the utility and limitations of a method of mechanically disaggregating BM trephine biopsies for FC. Method: Trephine biopsies mechanically disaggregated for FC between 2010 and 2016 were reviewed. We recorded cell yield, pathological findings, and turnaround time. Where available, results of trephine FC were compared with aspirate FC. Results: Eighty BM trephine samples were processed, representing 4.3% of BM biopsies. Mechanical disaggregation yielded cellular samples in 98% of cases (median yield 3 × 10 6 nucleated cells). The most frequent diagnoses were B cell lymphoproliferative disorders ( n = 26) and acute leukemia ( n = 18). Trephine FC correlated with histochemistry findings in 94% of cases, but two Hodgkin lymphoma infiltrates were missed by FC, and trephine FC underestimated B cell infiltrate burden compared to immunohistochemistry (IHC). Fluorescence intensity of CD34 and CD45 on disease populations was similar in processed trephine and contemporaneous aspirate samples. Trephine FC results were available 2 days earlier than stained IHC slides. Conclusion: Mechanical disaggregation of BM trephine samples provided a cellular suspension suitable for diagnostic FC in most cases. Limitations were similar to aspirate FC: disease burden was underestimated and some infiltrates were missed. Trephine FC results were available earlier than trephine IHC. We conclude that trephine FC is a useful technique to complement trephine IHC in the event of a failed aspirate, providing rapid diagnostic immunophenotyping. © 2018 International Clinical Cytometry Society